2019
DOI: 10.3390/foods8040120
|View full text |Cite
|
Sign up to set email alerts
|

Improved Lycopene Production from Different Substrates by Mated Fermentation of Blakeslea Trispora

Abstract: The production of lycopene from different substrates by Blakeslea trispora in fermentation was investigated. Lycopene productions from 4 and 6% glucose (pH 6.5) in shake flask fermentation were 77.7 and 28.1 mg L−1. Increasing the glucose concentration to 6% resulted in a decrease in lycopene production by 36.2%. A maximum lycopene concentration of 944.8 mg L−1 was detected with 4% glucose supplemented with 1.0 % sunflower oil in fermentor studies. Lycopene productions in the presence of sunflower and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
(42 reference statements)
0
32
0
Order By: Relevance
“…The industrial production of carotenoids has conventionally been conducted through an extraction from many natural products, such as tomato and watermelon [11]. However, the extraction method does not meet the growing demand due to limited supply of natural products [12,13]. In addition, its stable production is difficult because of fluctuating lycopene content of natural products: 0.00540-1.50 g lycopene/kg of tomato paste [14], method; however, there are also several critical limitations, including high production cost, low yield, and quality [12,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The industrial production of carotenoids has conventionally been conducted through an extraction from many natural products, such as tomato and watermelon [11]. However, the extraction method does not meet the growing demand due to limited supply of natural products [12,13]. In addition, its stable production is difficult because of fluctuating lycopene content of natural products: 0.00540-1.50 g lycopene/kg of tomato paste [14], method; however, there are also several critical limitations, including high production cost, low yield, and quality [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the extraction method does not meet the growing demand due to limited supply of natural products [12,13]. In addition, its stable production is difficult because of fluctuating lycopene content of natural products: 0.00540-1.50 g lycopene/kg of tomato paste [14], method; however, there are also several critical limitations, including high production cost, low yield, and quality [12,16]. To overcome those limitations, microbial production of lycopene has been studied as a promising strategy because it enables stable production through a simple and sustainable process [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The industrial production of carotenoids has conventionally been conducted through an extraction from many natural products, such as tomato and watermelon [11]. However, the extraction method does not meet the growing demand due to limited supply of natural products [12,13]. Besides, its stable production is difficult because of fluctuating lycopene content of natural products: 0.00540 -1.50 g lycopene/kg of tomato paste [14], 0.03 -0.07 g lycopene/kg of watermelon [15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, its stable production is difficult because of fluctuating lycopene content of natural products: 0.00540 -1.50 g lycopene/kg of tomato paste [14], 0.03 -0.07 g lycopene/kg of watermelon [15]. Chemical synthesis could be considered as an alternative method; however, there are also several critical limitations, including high production cost, low yield, and quality [12,16]. To overcome those limitations, microbial production of lycopene has been studied as a promising strategy, because it enables stable production through a simple and sustainable process [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Sevgili et al [8] checked the use of different substrates to produce lycopene via Blakeslea trispora fermentation. They confirmed that the medium with natural oil showed more lycopene than the medium that contained only a carbon source.…”
mentioning
confidence: 99%